QT interval and repolarization dispersion changes during the administration of hydroxychloroquine/chloroquine with/without azithromycin in early COVID 19 pandemic: A prospective observational study from two academic hospitals in Indonesia. Issue 5 (28th August 2021) - Gumilang, Rizki A.; Siswanto,; Anggraeni, Vita Y.; Trisnawati, Ika; Budiono, Eko; Hartopo, Anggoro B.
Abstract: Background: Hydroxychloroquine/chloroquine (HCQ/CQ) treatment for COVID‐19 was associated with QT interval prolongation and arrhythmia risks. This study aimed to investigate QTc interval and ventricular repolarization dispersion changes, as markers of arrhythmia risks, after HCQ/CQ administration with/without azithromycin (AZT) during COVID‐19 pandemic. Methods: A prospective observational study was performed in two academic hospitals in Indonesia. Adult patients who received HCQ/CQ alone and HCQ/CQ + AZT concomitant treatments for COVID‐19 infection were enrolled. Baseline and post HCQ/CQ treatment electrocardiograms were obtained. Baseline and post HCQ/CQ treatment QT interval by Bazett (B‐QTc) and Fridericia (F‐QTc) formulas and ventricular repolarization dispersion indices by Tpeak‐Tend (Tp‐e) interval and Tpeak‐Tend/QT (Tp‐e/QT) ratio were calculated and analyzed. Results: The study enrolled 55 (HCQ/CQ alone) and 77 subjects (HCQ/CQ + AZT concomitant). F‐QTc interval significantly lengthened in subjects with HCQ/CQ + AZT (mean difference 11.89 ms [ P  = .028]). The incidences of severe B‐QTc and F‐QTc lengthening were 13.1% and 12.3%, B‐QTc and F‐QTc prolongation were 25.4% and 12.3%, and severe B‐QTc and F‐QTc prolongation were 6.2% and 3.2%. Tp‐e interval lengthened significantly from baseline to posttreatment in HCQ/CQ alone and HCQ/CQ + AZT (mean difference 10.83 ms [ P  = .006] and 18.73 ms [ P  < .001], respectively). Tp‐e/QT ratio increased significantly from baseline to posttreatment in HCQ/CQ + AZT concomitant (mean difference 0.035 [ P  < .001]). No fatal arrhytmia occurred. Conclusions: During COVID‐19 pandemic, HCQ/CQ + AZT concomitant treatment caused significant F‐QTc lengthening, significantly increased Tp‐e interval and increased Tp‐e/QT ratio. HCQ/CQ alone only caused significant increase of Tp‐e interval. Incidences of severe QTc lengthening and prolongation were low in both HCQ/CQ alone and HCQ/CQ + AZT concomitant. Abstract : HCQ/CQ + AZT concomitant treatment caused significant F‐QTc lengthening, significantly increased Tp‐e interval and increased Tp‐e/QT ratio. Whereas, HCQ/CQ alone only caused significantly increased Tp‐e interval. The incidences of severe QTc lengthening and severe QTc prolongation, as well as arrhythmia, were similarly low in HCQ/CQ alone and HCQ/CQ + AZT concomitant.